2019
DOI: 10.3390/s19194160
|View full text |Cite
|
Sign up to set email alerts
|

About the Accuracy and Problems of Consumer Devices in the Assessment of Sleep

Abstract: Commercial sleep devices and mobile-phone applications for scoring sleep are gaining ground. In order to provide reliable information about the quantity and/or quality of sleep, their performance needs to be assessed against the current gold standard, i.e., polysomnography (PSG; measuring brain, eye, and muscle activity). Here, we assessed some commercially available sleep trackers, namely an activity tracker; Mi band (Xiaomi, Beijing, China), a scientific actigraph: Motionwatch 8 (CamNTech, Cambridge, UK), an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 18 publications
3
31
0
2
Order By: Relevance
“…Beyond adoption of sleep trackers by the general public, there is also growing interest from academic researchers and clinicians to better understand how to utilize sleep tracking data from consumer devices [ 6 , 10 ]. Early evidence indicated that consumer-grade sleep trackers have promise as tools for large scale sleep studies [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond adoption of sleep trackers by the general public, there is also growing interest from academic researchers and clinicians to better understand how to utilize sleep tracking data from consumer devices [ 6 , 10 ]. Early evidence indicated that consumer-grade sleep trackers have promise as tools for large scale sleep studies [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research around sleep tracking shows increased anxiety around sleep performance as a result is not uncommon (Baron et al, 2017). But research in sleep trackers also shows us how inaccurate they are (Ameen et al, 2019;Tuominen et al, 2019;Louzon et al, 2020). This is a conundrum for design, raised previously in a discussion about the "accuracy" of scales for supporting weight management (Kay et al, 2013): are we achieving what we hope to achieve for health with this dataled approach?…”
Section: Insourcing To Outsourcing Lens Of Interactive Health Techmentioning
confidence: 99%
“…In research, self-perceived sleep quality is considered to be a more important marker of success rather than duration (quantity) (Choe et al, 2015a) alone (Mary et al, 2013;Mander et al, 2017;Manzar et al, 2018). Thus, our heuristics/ experiments focused on practices that were assessed on a qualitative and experiential basis, rather than the currently dominant and possibly inaccurate (Ameen et al, 2019;Tuominen et al, 2019;Louzon et al, 2020) tracking approach of hours slept, number of interruptions, time assumed to be in a particular sleep state and so on. Our focus was: after trying this heuristic, how do you feel?…”
Section: Study Two: Sleepbetter-many Paths To Healthmentioning
confidence: 99%
“…Participants wore an activity monitoring bracelet on the wrist of their nondominant hand every night. Daily sleep duration was monitored by a commercially available wrist-worn sleep/activity tracker, Mi band 2 [23]. Moderate intraclass correlation coefficients (ICC) of 0.62-0.75 have been reported for the Mi Band 2 sleep duration assessment [24].…”
Section: Sleep Monitoringmentioning
confidence: 99%